2016
DOI: 10.1111/ncmr.12066
|View full text |Cite
|
Sign up to set email alerts
|

Building Strength or Lending an Ear in Legal Conflicts: Dependence and Conflict Asymmetry as Distinct Predictors of Needs for Support

Abstract: Being aware of psychological aspects of legal conflicts can benefit the efficiency of legal aid. We propose that needs for support may be particularly dependent upon the experience of asymmetry between conflict parties. We distinguish between two types of asymmetry and examine how they relate to different needs for support. We hypothesized that dependence asymmetry (being more dependent on the other party than vice versa) would predict a need for problem‐focused help. Conflict asymmetry (experiencing more conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 83 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…The resulting dataset included 312 individuals, of which 260 in the test group and 52 in the control group on the first measurement (T 1 ), 183 and 46 on the second measurement (T 2 ), and 137 and 35 on the last measurement (T 3 ) respectively 7 (Van Dijk et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting dataset included 312 individuals, of which 260 in the test group and 52 in the control group on the first measurement (T 1 ), 183 and 46 on the second measurement (T 2 ), and 137 and 35 on the last measurement (T 3 ) respectively 7 (Van Dijk et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggests that in legal conflicts, the need for third-party help is higher for individuals who perceive a power disadvantage (Van Dijk et al, 2016). If a third party is a good fit, help can be beneficial, especially to low power holders (Bryan, 1999; Shestowsky, 2020; Ting-Toomey et al, 2000).…”
Section: Perceptions Of Power Asymmetry In Divorcementioning
confidence: 99%
See 1 more Smart Citation
“…Survey studies, controlled laboratory experiments, and interviews with students are interesting, but she argues that these are less suitable for the safety and security field; that is, self‐reports are often distorted (people not willing or able to accurately evaluate), and it is difficult to integrate low‐trust, high‐stakes circumstances in a laboratory situation, and the behavioral patterns under study are usually complex. Consequently, she works in close collaboration with many organizations to stay connected to practice as much as possible, such as the police (Beune et al., ), the military (De Graaff, Giebels, Meijer, & Verweij, ), and the council of legal aid (Van Dijk et al., ). Assessing these studies reveals that Ellen found solutions to integrate experimental set‐ups in practice, which underlines her argument that fieldwork and experimental rigor are not antithetical.…”
Section: Working With Ellen: the Interaction Between Theory And Practmentioning
confidence: 99%
“…Because social conflicts can be a major problem in deteriorated neighborhoods, Elze Ufkes studied social categorization, negative emotions, behavioral intentions of residents, and mediation in neighbor‐to‐neighbor conflict (Ufkes, Giebels, Otten, & Van Der Zee, ; Ufkes, Otten, Van der Zee, & Giebels, ). Together with PhD student Marian van Dijk, Ellen studies conflicts in a legal setting, and how conflict and dependence asymmetry affect the preferred type of support people prefer in legal conflicts (Van Dijk, Giebels, & Zebel, ). These examples make clear that Ellen studies high‐stakes conflicts across different settings.…”
mentioning
confidence: 99%